2016
DOI: 10.2174/1874325001610010439
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in a Multimodal Blood Loss Prevention Protocol to Decrease Blood Loss in Revision Total Knee Arthroplasty: A Cohort Study

Abstract: Purpose: To clarify if blood loss and transfusion requirements can be decreased in revision knee surgery through a multimodal blood loss approach with tranexamic acid (TXA)Patients and Methods: A retrospective study was designed in 87 knees (79 patients) that received a knee revision between 2007 and 2013. To avoid heterogeneity in the surgical technique, only revisions with one single implant system were included. A treatment series of 44 knees that received TXA and other techniques in a multimodal blood loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…However, few clinical studies have evaluated the safety and effectiveness of TXA for reducing blood loss during the perioperative period in revision TKA. We only identified five retrospective studies and no prospective studies on the use of TXA in revision TKA …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few clinical studies have evaluated the safety and effectiveness of TXA for reducing blood loss during the perioperative period in revision TKA. We only identified five retrospective studies and no prospective studies on the use of TXA in revision TKA …”
Section: Discussionmentioning
confidence: 99%
“…11.0 (NCSS Statistical Software). Based on previous observations in our orthopedic department and data from retrospective studies of TXA in revision TKA, we assumed a hemoglobin difference of 1.0 g/dL and a standard deviation of 1.5 g/dL with an assumed two‐sided α value of 5% and a power of 80%. Therefore, a minimum sample size of 74 patients was required for this study (37 per group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thromboembolic complications, such as DVT or PE, were reported in three studies [10, 12, 13]. Two included studies reported that revision components were implanted in both the femur and the tibia [10, 11]. The other two studies stated patients were undergoing revision of two components, revision of one component, or an isolated liner exchange.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, TXA has been widely used in patients undergoing primary joint replacement, and the proportion of patients requiring transfusion during the perioperative period has also been significantly reduced [11,12]. Although sufficient studies have confirmed that TXA can effectively reduce the perioperative blood loss and transfusion rate in pTJA, large trials to study the role of TXA in rTJA are still lacking [13][14][15]. To clarify this issue, we conducted a meta-analysis to assess whether TXA could play an active role in rTJA.…”
Section: Introductionmentioning
confidence: 99%